2016
DOI: 10.1515/jbnst-2015-1018
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Banking Crises

Abstract: This paper compares determinants of banking sector crises using an early warning system approach in a diverse cross-country panel. We cover 152 countries using annual data from 1990 to 2011. We provide three main contributions: (i) accommodating different influences on banking sector fragility (banking sector, macroeconomic and structural features) in a wide country panel; (ii) introducing a variable accounting for geographical contagion effects; and (iii) cross country comparison based on two subsamples: adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
0
0
Order By: Relevance
“…However, the influence was statistically insignificant in the two models. From the negative sign of that variable, those findings contradict Fendel and Stremmel (2016), who found that financial deepening lowers the likelihood of a banking crisis. However, when the financial deepening is measured by the ratio of domestic credit to GDP, whereas the domestic credit is also part of M2, an increase in that ratio will raise the possibility of a banking crisis, as also suggested by Gupta and Kashiramka (2020).…”
Section: Robustness Checkmentioning
confidence: 64%
“…However, the influence was statistically insignificant in the two models. From the negative sign of that variable, those findings contradict Fendel and Stremmel (2016), who found that financial deepening lowers the likelihood of a banking crisis. However, when the financial deepening is measured by the ratio of domestic credit to GDP, whereas the domestic credit is also part of M2, an increase in that ratio will raise the possibility of a banking crisis, as also suggested by Gupta and Kashiramka (2020).…”
Section: Robustness Checkmentioning
confidence: 64%